2004
DOI: 10.1152/jn.00425.2004
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Controlled Plasticity at GluR2-Deficient Synapses Onto Hippocampal Interneurons

Abstract: Laezza, Fernanda and Raymond Dingledine. Voltage-controlled plasticity at GluR2-deficient synapses onto hippocampal interneurons. J Neurophysiol 92: 3575-3581, 2004; doi:10.1152/jn.00425.2004. High-frequency stimulation of pyramidal cell inputs to developing (P9-12) hippocampal stratum radiatum interneurons expressing GluR2-lacking, Ca 2ϩ -permeable AMPA receptors produces longterm depression of synaptic transmission, if N-methyl-D-aspartate (NMDA) receptors are blocked. Here we show that these same synapses d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…6 A). Low-frequency stimulation of inputs at a holding potential of 0 mV or delivering tetanic stimulation at a holding potential of Ϫ30 mV to enhance calcium influx via NMDARs (Laezza et al, 1999;Laezza and Dingledine, 2004) did not reveal any dependence of LTP on NMDARs. Thus, low-frequency pairing at 0 mV did not evoke LTP, whereas tetanic stimulation at Ϫ30 mV did evoke LTP but was not blocked by D-APV (data not shown).…”
Section: Ltp Requires Trafficking Of Ampa Receptors and Sap97mentioning
confidence: 81%
“…6 A). Low-frequency stimulation of inputs at a holding potential of 0 mV or delivering tetanic stimulation at a holding potential of Ϫ30 mV to enhance calcium influx via NMDARs (Laezza et al, 1999;Laezza and Dingledine, 2004) did not reveal any dependence of LTP on NMDARs. Thus, low-frequency pairing at 0 mV did not evoke LTP, whereas tetanic stimulation at Ϫ30 mV did evoke LTP but was not blocked by D-APV (data not shown).…”
Section: Ltp Requires Trafficking Of Ampa Receptors and Sap97mentioning
confidence: 81%
“…It has been previously shown that glutamatergic inputs onto interneurons containing CP-AMPARs display smaller NMDAR-mediated components than synapses containing CIAMPARs (Angulo et al, 1999;Lei and McBain, 2002;Laezza and Dingledine, 2004;Lamsa et al, 2007). Does this principle apply to DG PIIs?…”
Section: Afferent-specific Expression Of Ca 2؉ -Permeable Ampar and Nmentioning
confidence: 99%
“…Requires NMDARs and CP-AMPARs. Induced when postsynaptic Vm allows simultaneous activation of both receptors (Laezza and Dingledine, 2004).…”
Section: Ca3mentioning
confidence: 99%